Association of a newly proposed dietary index for gut microbiota with phenotypic age acceleration: a cross-sectional study of NHANES 1999–2018 - Boming Xu; Yingxuan Huang; Yilin Zeng; Peizhong Chen; Yubin Wang; Xiaoqiang Liu (Journal of Health, Population and Nutrition)
Abstract Background Aging is closely linked to chronic diseases, and gut microbiota plays a significant role in this process. The Dietary Index for Gut Microbiota (DI-GM), a novel tool reflecting the potential impact of diet on gut microbiota diversity, has an unclear association with biological aging. This study aimed to evaluate the association between DI-GM and phenotypic age acceleration (PAA), revealing the potential regulatory effect of diet on aging. Methods Data from 29,435 participants in NHANES 1999–2018 were analyzed using multivariable regression models to assess the association between DI-GM scores and PAA. Phenotypic age was estimated from 10 physiological indicators, with PAA defined as a positive age acceleration residual (ACR). DI-GM was constructed from 14 dietary components; higher scores indicate greater potential benefits to gut microbiota. Results Higher DI-GM scores were significantly associated with a lower risk of PAA. After adjusting for covariates, each 1-point increase in DI-GM was linked to a 7% reduction in PAA risk (OR = 0.93, 95% CI = 0.91–0.95, P < 0.001) and a decrease of 0.33 in ACR (β = -0.33, 95% CI = -0.39 to -0.26, P < 0.001). Subgroup and sensitivity analyses confirmed these findings. Conclusions Higher DI-GM scores are significantly associated with reduced phenotypic age acceleration. Dietary improvements that promote gut microbiota health may effectively delay aging, providing scientific evidence for dietary interventions aimed at healthy aging.